A Limit Theorem for Integral Functionals of an Extremum of Independent Random Processes - Matsak, I. K.; Мацак, І. К. (Institute of Mathematics, NAS of Ukraine, 2005)
We prove a theorem on the convergence of integral functionals of an extremum of independent stochastic processes to a degenerate law of distributions.